The effect of moral pressures and the threat of personal interests on auditors’ professional judgment and doubt - Hoseini , Shahamat; Sheybani, Abbas; Shafiei , Hosein (Social Determinants of Health, 2024)
Background: One of the most important factors that can affect auditors’ understanding of ethical issues is the environmental factor of the threat to personal interests. The objective of this research was to examine the impact of ethical constraints and personal interest threats on professional judgment and doubt. Methods: The use of field research and documentation has been made to apply the goal of this study and the descriptive-correlation approach. To determine the research pattern and the criteria extracted from the theoretical bases has been done with the help of 30 experts using the method based on the Delphi technique. The statistical population of this research was the auditors working in member institutions of the official accountants’ society at different levels. Factor load, path coefficients, Cronbach’s alpha coefficient and composite reliability coefficient were stimated. All statistical analyses were done using SPSS and Amos software. Results: In every instance, the T value and the standardized factor loading between the variables and the questions were more than 1.96 and 0.4, respectively. Consequently, the findings demonstrated that the questions were appropriately included in the model and study based on the data gathered, and no more questions in the questionnaire needed to be added or altered. Ethical pressures and the threat of personal interests have a significant effect on auditors’ judgment and auditors’ professional skepticism. Also, the threat of personal interests has a significant effect on professional doubt. Average variance extracted showed that the appropriateness of convergent validity because the average variance retrieved from the elements. Factor loading coefficients showed that the self-interest item had the highest coefficient. Conclusion: Moral pressures and the threat of personal interests are important factors in auditors’ judgments and their professional doubts, which are effective from the cultural resources of the society. Therefore, adjusting each of these factors will improve the conditions of auditors.